Case Study: Rural Tourism in Antilla for Local Development - Lisbet Eunice Pérez Anzardo; Frank Antonio González Aguilera; Rosa Isidora Palao Fuentes; Olga Lidia Ortiz Pérez (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
Rural tourism is a strategic for preserving local identity and revitalizing agricultural economies. The municipality of Antilla, in Holguín, Cuba, was selected as a case study due to its underutilized agro-productive and cultural resources and reliance on the traditional sun-and-beach modality. This research aimed to design the Rural Paradise Route by integrating endogenous resources to foster local development and provide a replicable model for Cuban rural destinations. The methodological procedure of Pérez & Cardet (2022) was applied, complemented by theoretical methods (historical-logical, analytical-synthetic, inductive-deductive) and empirical techniques such as documentary review and unstructured interviews with state and non-state tourism actors. Results show that Antilla possesses significant but underexploited potential, whose articulation into a rural tourism product can diversify the destination’s portfolio and strengthen community identity. Validated by specialists as viable and innovative, it demonstrates how participatory methodologies can integrate agro-productive and cultural value chains, offering practical implications for diversifying tourism.